PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT CHARINDO PALMA OETAMA LANDAK - B11111053, Ledia Agustina (Jurnal Manajemen Update, 2015)
The purpose of this Study was to determine the influence of organizational culture and work discipline on the employee’s performance at PT. Charindo Palma Oetama Landak. This type of research is causal research and survey research. Data collection techniques researchers used primary data and secondary data. The data analysis technique used is the technique of multiple linear regression analysis, processed using SPSS version 16. Hypothesis testing is done by distributing questionnaires to 65 employees of the PT. Charindo Palma Oetama Landak. The results showed that there was a positive influence of the organizational culture variable (X1) on the employee performance (Y) as it evidenced by the significance value of 0,049 t is smaller than 0,05. There is a positive influence of the work discipline variabel (X2) on the employee performance (Y) as it evidenced by the significance value of 0,028 t is smaller than 0,05. Keywords : employee performance, organizational culture and work discipline